Creatine kinase during non-ST-segment elevation acute coronary syndromes is associated with major bleeding - Brewster, Lizzy Maritza (Open Heart, 2020)
BACKGROUND: It was recently reported that highly elevated plasma activity of the ADP-scavenging enzyme creatine kinase (CK), to >10 times the upper reference limit (URL), is independently associated with fatal or non-fatal bleeding during treatment for ST-segment elevation myocardial infarction (OR 2.6 (95% CI, 1.8 to 2.7)/log CK increase). Evidence indicates that CK attenuates ADP-dependent platelet aggregation. This study investigates whether moderately elevated CK in non-ST-segment elevation acute coronary syndrome (NSTE-ACS) is associated with major bleeding. METHODS: The Thrombolysis In Myocardial Ischemia (TIMI) 3B trial compared recombinant tissue-type plasminogen activator (rt-PA) (35–80 mg) with placebo and early catheterisation with conservative management in patients with NSTE-ACS. Main outcomes of the current study are the independent association of peak plasma CK (CKmax) with adjudicated fatal or non-fatal major bleeding (primary) and with combined major bleeding, stroke and hospital death (secondary), with covariables including age, sex, body mass index, systolic blood pressure, creatinine and assignment to add-on rt-PA versus placebo. Discrimination was assessed with C-statistics. RESULTS: The study included 1473 patients (66% men, 80% white, mean age 59 years, SE 0.3). CKmax ranged between 15 and 19 045 IU/L (mean (SE), 450 (24) IU/L; two times URL). Major bleeding occurred in 2.0% (mean age 65 (1.3) years; mean CKmax 1015 (319) IU/L; six times URL), and the combined outcome in 4.3% of the patients, adjusted OR per log CK increase, respectively, 3.1 (1.6 to 5.9) for major bleeding and 3.9 (2.5 to 6.1) for the combined outcome; C-index 0.8 for both outcomes. The association between CK and bleeding was independent of the use of thrombolytic therapy. DISCUSSION: The presented data add to the existing evidence that proportionate to its plasma activity, the ADP-binding enzyme CK is strongly and independently associated with non-fatal and fatal major bleeding during treatment for NSTE-ACS. CK might increase the accuracy of prediction models for major bleeding in patients with NSTE-ACS. TRIAL REGISTRATION NUMBER: NCT00000472.